2022
DOI: 10.1155/2022/1815170
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Public Big Data Management under Text Analysis

Abstract: Based on text analysis, public big data management is studied. The public data management of Mount Wutai tourism network travel notes is discussed. The positive, neutral, and negative effects of the naive Bayesian classification model and decision tree classification model on the tourism sentiment attitude of Mount Wutai are compared. The relationship between tourism resources, tourism facilities, tourism services, tourism environment, and tourism sentiment and attitude of Wutai Mountain is analyzed. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The DEA is a great way to learn about the human resources and potential of coal production in China. Some scholars use the DEA method to determine that “finance is the most important factor affecting the performance of China's high-tech industry and human technology” [ 9 ]. He hoped that China's high-tech industry will continue to benefit from the application of science and technology of human resources in the field of performance measurement, innovation baking, and financial management.…”
Section: Introductionmentioning
confidence: 99%
“…The DEA is a great way to learn about the human resources and potential of coal production in China. Some scholars use the DEA method to determine that “finance is the most important factor affecting the performance of China's high-tech industry and human technology” [ 9 ]. He hoped that China's high-tech industry will continue to benefit from the application of science and technology of human resources in the field of performance measurement, innovation baking, and financial management.…”
Section: Introductionmentioning
confidence: 99%
“…Posterior probabilities were estimated by each heterogeneous information source, representing the possibilities of targets and non-targets. The true positive rate (TPR) and true negative rate (TNR) combined with the posterior probabilities provided evidence for the three hypotheses (target, non-target and uncertain) (Zhu and Kan, 2022). Then, evidence was fused using the D-S combination rule.…”
Section: Fusion Methods Of Computer Vision and Human Vision Based On ...mentioning
confidence: 99%
“…The TPR and TNR represent the detection capabilities of targets and non-targets, respectively. In addition, the false positive rate (FPR) is another performance metric that refers to the probability of falsely identifying the non-target as the target (Zhu and Kan, 2022). The above indicators are calculated from the confusion matrix, and an illustration of the confusion matrix is shown in Figure 4.…”
Section: Dynamic Probability Integrationmentioning
confidence: 99%
“…The experimental results showed that the tree long short-term memory network (LSTM) model had a higher F1 value than Bi LSTM in sentiment classification by 1.19% and had a higher classification ability for tourism reviews [ 4 ]. Zhu compared the positive, neutral, and negative effects of the plain Bayesian classification model and the decision tree classification model on the emotional attitude toward tourism in Wutai Mountain [ 5 ]. The experimental results showed that good results were achieved on a self-built dataset for the evaluation of tourist attractions in Wutai Mountain.…”
Section: Related Workmentioning
confidence: 99%